Sequential percutaneous intervention for sinus venosus defect and significant coronary artery disease - Bojja Venkata Satya Roopesh; Kothandam Sivakumar; Pramod Sagar; Ajit Sankardas Mullasari (Annals of Pediatric Cardiology)
Superior vena cava (SVC) type of sinus venosus defect (SVD) associated with anomalous right upper pulmonary vein (RUPV) drainage is often corrected by open-heart surgery. Transcatheter-covered stent exclusion is an attractive emerging alternative using a covered stent in the lower end of SVC to close the SVD and redirect the RUPV to the left atrium. The location of SVD posterosuperior to oval fossa challenges its transthoracic echocardiographic identification and delays its diagnosis to adult age. Lifestyle adult diseases, including atherosclerosis, elevate the left ventricular end-diastolic pressures and increase the pretricuspid left-to-right shunt. Surgery addresses coronary stenosis and SVD, but lifestyle diseases increase surgical risks. We diagnosed significant coronary stenosis in three patients with SVD. These patients underwent percutaneous management of both lesions. Nonsurgical management of SVD and ischemic heart disease is a more viable alternative than a high-risk surgery in adults with comorbidities.